Sistem Informasi Pelayanan Pendaftaran Peserta KB Berbasis Web pada Puskesmas Wee Karou di Kabupaten Sumba Barat - Vinansa Louru Dairu; Adelbertus Umbu Janga; Mitra Permata Ayu (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The Web-Based Information System for Family Planning (FP) Participant Registration at the Wee Karou Community Health Center in West Sumba Regency aims to simplify the registration process for FP participants, improve efficiency, and provide easier access for the community to FP services. Previously, the registration process was conducted manually, which often led to delays, data processing errors, and time inefficiency. Therefore, an information system is needed to digitalize the registration and data management processes of FP participants. This system is developed using web-based technology that enables the Wee Karou Health Center to conduct online FP participant registration, monitor program progress, and generate reports more quickly and accurately. The main features of the system include online FP participant registration, participant data management, service schedule monitoring, and the generation of statistical reports related to FP services. The implementation of this system is expected to reduce data entry errors, accelerate the registration process, and enhance transparency and data accuracy. In addition, it provides convenience for the community to register without having to visit the health center directly. Thus, the Family Planning services at Wee Karou Community Health Center are expected to become more optimal, effective, and efficient in supporting government programs for population control and better family planning.